Resolusi Konflik Sengketa Lahan Hutan Tanaman Industri (Hti) Di Kampung Mandiangin Kecamatan Minas Kabupaten Siak - Tarisa Wulandari; Abdul Sadad (Bahasa Indonesia, 2022)
Currently, the Indonesian government is still not able to solve the problems of land conflicts that occur in Indonesia. Various conflicts that occur in several areas, one of which is in the concession area of ​​Industrial Planting Forests (HTI). One of the areas where industrial forest land disputes (HTI) are conflicted is Mandiangin Village with private parties such as PT. Eternal Arra. The problem begins with a claim between the community and the private sector. This study uses qualitative research through a phenomenological approach. Data collection in this study used observation, interviews and documentation techniques. Furthermore, using the analysis technique of (Cresswell, 2007). This study uses the Resolution theory proposed by Fisher in (Fina, 2017) namely Negotiation, Mediation, and Arbitration. The results showed that the efforts of KPHP as a third party who had no interest in the two had not yet reached the stage of finding results, because one of the conflicting parties did not follow the course of the process. So that the next stage has not been carried out and the efforts made by KPHP to Mandiangin Village have not been able to run optimally.